Emergent Enhanced Electrocaloric Effect within Wide Temperature Span in Laminated Composite Ceramics. (20th October 2021) - Yin, Ruowei; Li, Junjie; Su, Xiaopo; Qin, Shiqiang; Yu, Chengye; Hou, Yuxuan; Liu, Chuanbao; Su, Yanjing; Qiao, Lijie; Lookman, Turab; Bai, Yang
Abstract: An outstanding challenge for high‐efficient and zero‐emissions ferroelectric refrigeration is to maintain a large adiabatic temperature change (Δ T ) over a wide temperature span ( T span ) resulting from the electrocaloric effect (ECE). A multilayer ferroelectric structure with interlayer synergistic phase transitions as a means to address this problem is proposed. BaTi0.89 Sn0.11 O3, BaTi0.85 Zr0.15 O3, and BaTi0.89 Hf0.11 O3 were selected as the components of each layer, the compositions of which are fixed at the tricritical point (TP) in each system and where the transition temperatures increase sequentially. Ferroelectrics near TP have a high sensitivity to external fields and the good co‐firing adhesion leads to strong electrical and stress interface coupling between adjacent layers. The electric‐field‐induced phase transition in one layer then synergistically induces a phase transition in the near interface part of the adjacent layer, which is close to but is not at the transition point yet. As a result, the enhanced ECE performance, including both a large Δ T max = 0.63 K and a wide T span = 57 °C (Δ T ≥ 80% Δ T max ), exceeds that associated with the sum of the individual components. An efficient composite materials design strategy to develop high‐performance electrocaloric materials with excellent ECE properties for practical refrigeration applications is thus proposed. Abstract : A multilayer structure with three compositions at the tricritical point, and with transition temperatures that increase sequentially is proposed. The significant interaction between adjacent layers dynamically utilizes the larger thermal response of the adjacent temperature domain by a synergistic phase transition, resulting in a large EC response (Δ T max = 0.63 K) and wide temperature span (57 °C).